2019
DOI: 10.1177/1043659619881491
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Sleep Disturbance Among Female Nurses: Anxiety or Depression?

Abstract: Introduction: Sleep quality is an important issue in nurses’ mental and general health. Long-term psychological distress leads to increased sleep disturbances among nurses. However, which forms of psychological distress are most associated with sleep disturbances is unclear among female nurses. Methodology: To determine which psychological distress factors are associated with sleep disturbances among female nurses. A total of 119 female Taiwanese nurses were recruited and surveyed using the Occupational Stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 31 publications
4
28
1
1
Order By: Relevance
“…In our primary analysis, frustration with technology was found to be associated with burnout independently of other markers of WLI. This association was not as strong as the one observed for difficulty sleeping, consistent with observations that sleep disturbance may itself be an indicator of psychological distress [ 55 ]. However, it was similar in magnitude to the associations for other items reflecting excessive workload or workplace inefficiencies, such as changing personal/family plans because of work, working a shift without any breaks, or arriving home late from work.…”
Section: Discussionsupporting
confidence: 80%
“…In our primary analysis, frustration with technology was found to be associated with burnout independently of other markers of WLI. This association was not as strong as the one observed for difficulty sleeping, consistent with observations that sleep disturbance may itself be an indicator of psychological distress [ 55 ]. However, it was similar in magnitude to the associations for other items reflecting excessive workload or workplace inefficiencies, such as changing personal/family plans because of work, working a shift without any breaks, or arriving home late from work.…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies have shown that unhealthy lifestyles (poor sleep quality, depression, and conscious health impact, etc.) caused by busy work, high loads and high pressure will increase the intention of nursing staff to turnover and leave the job [ 5 ], and have found that especially the quality of sleep and depression have a great impact on the mental health and overall health of nursing staff [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Family factors, such as being married, further increased the risk of night shift-related sleep impairment due to increased family responsibilities ( Booker et al, 2018 ). The majority of nurses were female; a study of female nurses found that psychological distress, especially depression, was associated with sleep disturbance ( Chueh et al, 2021 ). Meanwhile, menopause-related symptoms also greatly influenced sleep quality ( Pien et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%